1998
DOI: 10.1090/s0002-9939-98-04598-5
|View full text |Cite
|
Sign up to set email alerts
|

Duality for full crossed products of 𝐶*-algebras by non-amenable groups

Abstract: Abstract. Let (A, G, δ) be a cosystem and (A, G, α) be a dynamical system. We examine the extent to which induction and restriction of ideals commute, generalizing some of the results of Gootman and Lazar (1989) to full crossed products by non-amenable groups. We obtain short, new proofs of Katayama and Imai-Takai duality, the faithfulness of the induced regular representation for full coactions and actions by amenable groups. We also give a short proof that the space of dual-invariant ideals in the crossed pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…This follows from the work of Raeburn, [27], who showed that the full crossed product, defined by universal properties, is isomorphic to the reduced crossed product that we have defined here. The papers [7,18,20,22,27] are good references for background material.…”
Section: Preliminariesmentioning
confidence: 99%
“…This follows from the work of Raeburn, [27], who showed that the full crossed product, defined by universal properties, is isomorphic to the reduced crossed product that we have defined here. The papers [7,18,20,22,27] are good references for background material.…”
Section: Preliminariesmentioning
confidence: 99%
“…Hence, this assumption is necessary for our proof to work. That prefixInd restricted to double-struckIBtrueα̂Ĝfalse(Bfalse) coincides with i is proved in [26, Proposition 3.14(iii)] if G amenable (see also [47, Proposition 3.1(iii)], where the full crossed products are considered).…”
Section: Group Actions and Regular Inclusionsmentioning
confidence: 95%
“…Remark It is known that a diagram similar to () commutes when i is replaced by the map prefixInd given by kernels of the corresponding induced representations (see [26, Remarks 2.8] or [47, Propositions 2.7 and 2.8]). Thus, we need to show that prefixInd and i coincide on restricted ideals.…”
Section: Group Actions and Regular Inclusionsmentioning
confidence: 99%
“…Remark 3.24. Certainly the extension of [39, Corollary 2.2] to non-separable systems does not require the heavy machinery of coactions, as it happens in [76,Corollary 3.4 (i)]. Nevertheless we have not able to locate an appropriate reference in the literature that does not involve coactions.…”
Section: Now Ifmentioning
confidence: 98%